Dynamic microwave-assisted extraction combined with continuous-flow microextraction for determination of pesticides in vegetables. (1st February 2016) - Wu, Lijie; Hu, Mingzhu; Li, Zhanchao; Song, Ying; Yu, Cui; Zhang, Hanqi; Yu, Aimin; Ma, Qiang; Wang, Ziming
Highlights: A novel DMAE–CFME was firstly assembled and validated for extraction of OPPs in vegetables. Extraction, separation, and enrichment were finished in a simple step. The method extends the application of the SDME in complex solid matrixes. No further filtration or cleanup was required before analysis by GC–MS. The developed method is simple, rapid, solventless and cost-effective. Abstract: A simple, rapid, solventless and cost-effective dynamic microwave-assisted extraction (DMAE) combined with continuous-flow microextraction (CFME) system was firstly assembled and validated for extraction of eight organophosphorus pesticides in vegetables. The method combines the advantages of DMAE and CFME, and extends the application of the single drop microextraction to complex solid samples. The extraction, separation, and enrichment were performed in a single step, which could greatly simplify the operation and reduce the whole pretreatment time. In the developed method, analytes were first extracted from the vegetables using 3% NaCl solution as extraction solvent, then concentrated into microextraction solvent. After extraction, the microextraction solvent containing the enriched analyte was directly analyzed by GC–MS without any filtration or clean-up process. Several parameters affecting the extraction efficiency were investigated and optimized. Real vegetable samples were analyzed, satisfactory recoveries were obtained in the range of 80.7–106.7%, and relative standard deviations were lower than 8.7%.